2021
DOI: 10.1101/2021.11.16.21266115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rhinovirus-induced epithelial RIG-I inflammasome activation suppresses antiviral immunity and promotes inflammatory responses in virus-induced asthma exacerbations and COVID-19

Abstract: Rhinoviruses (RV) and inhaled allergens, such as house dust mite (HDM) are the major agents responsible for asthma onset, its life-threatening exacerbations and progression to severe disease. The role of severe acute respiratory syndrome coronavirus (SARS-CoV-2) in exacerbations of asthma or the influence of preexisting viral or allergic airway inflammation on the development of coronavirus disease 2019 (COVID-19) is largely unknown. To address this, we compared molecular mechanisms of HDM, RV and SARS-CoV-2 i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 136 publications
(227 reference statements)
0
16
0
Order By: Relevance
“…dpi. 59 This may be attributed to the different temporal dynamics of infection (i.e., time-points), different models used (i.e., in vitro and in vivo), and viral clearance by immune cells. Therefore, it is crucial to also investigate the role of peripheral blood mononuclear cells (PBMCs) in viral clearance and the cross-talk with antiviral-signaling in infected hNECs or hBECs of healthy control and asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…dpi. 59 This may be attributed to the different temporal dynamics of infection (i.e., time-points), different models used (i.e., in vitro and in vivo), and viral clearance by immune cells. Therefore, it is crucial to also investigate the role of peripheral blood mononuclear cells (PBMCs) in viral clearance and the cross-talk with antiviral-signaling in infected hNECs or hBECs of healthy control and asthmatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 RNA is recognized by MDA5 47 . Infection with RV initiates type I/III IFN response, therefore pre-infection with rhinovirus reduces SARS-CoV-2 replication 48 , but RV and SARS-CoV-2 co-infection leads to the greater damage of airway epithelium, especially in patients with asthma 21 . An observed ACE2 increase was caused presumably by an increase in short ACE2 mRNA, as we demonstrated above.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, infection with rhinovirus (RV), the most common exacerbation-inducing factor in asthma, has been shown to inhibit SARS-CoV-2 infection via type I/III IFN-dependent mechanism [18][19][20] , which might suggest that this mechanism could constitute some form of protection. However, we recently reported that co-infection of rhinovirus (RV) and SARS-CoV-2 leads to a greater retinoic acid-inducible gene I (RIG-I) inflammasome-dependent damage of airway epithelium in patients with asthma 21 , which is strongly supported by the clinical findings that patients with RV and SARS-CoV-2 coinfection are more prone to severe COVID-19 22 . Finally, some components of house dust mite (HDM) or birch pollen allergens were demonstrated to decrease type I/III IFN responses 21,23 at the mucosal sites, a mechanism which may potentially contribute to the reported correlations between high allergen exposure and increased SARS-CoV-2 infection rates 24 .…”
Section: Introductionmentioning
confidence: 92%
“…The RIG-I inflammasome is activated in primary lung epithelial cells and peripheral blood mononuclear cells. Furthermore, the activation of the epithelial RIG-I inflammasome is implicated in virus-induced inflammatory responses 47 .…”
Section: Discussionmentioning
confidence: 99%